WEWENANG DISKRESI KEPOLISIAN DALAM PENEGAKAN HUKUM DI BIDANG LALU LINTAS BERDASARKAN PASAL 18 UNDANG-UNDANG NOMOR 2 TAHUN 2002 TENTANG KEPOLISIAN (STUDI KASUS DI POLRES KABUPATEN KEDIRI) - FH, Suharto (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 1 No 02 (2021): Desember 2021DO - 10.32503/ammer.v1i02.2184, 2021)
The purpose of this study is to determine the limits of police discretion according to Article 18 of Law No. 2 of 2002 concerning the Police and to determine the forms of discretion that are allowed according to Law No. 2 of 2002. The results of the study explain that the Kediri District Police officers have behaved well. to violators. For child violators, the treatment from the authorities is different. There are officers who smile, get angry, and show a firm attitude without compromise. This action was taken by the authorities to anticipate traffic violations. Officials from the Kediri District Police also conduct traffic patrols to carry out road surveillance with a view to maintaining order on the highway in accordance with existing regulations, so that it can be used safely and effectively. Police discretion is basically the authority of the Police which is rooted in the principle of Police General Obligations, which is a principle that gives authority to police officers to act or not act according to their own judgment, in the context of their general obligations to maintain, maintain order and ensure public security.